Disparities in the gut metabolome of post-operative Hirschsprung's disease patients - Vera Plekhova (Nature Portfolio, 2021)
Abstract Hirschsprung's disease (HD) is a congenital structural abnormality of the colon seen in approximately 1 to 5000 live births. Despite surgical correction shortly after presentation, up to 60% of patients will express long-term gastrointestinal complaints, including potentially life-threatening Hirschsprung-associated enterocolitis (HAEC). In this study fecal samples from postoperative HD patients (n = 38) and their healthy siblings (n = 21) were analysed using high-resolution liquid chromatography—mass spectrometry aiming to further unravel the nature of the chronic gastrointestinal disturbances. Furthermore, within the patient group, we compared the faecal metabolome between patients with and without a history of HAEC as well as those diagnosed with short or long aganglionic segment. Targeted analysis identified several individual metabolites characteristic for all HD patients as well as those with a history of HAEC and long segment HD. Moreover, multivariate models based on untargeted data established statistically significant (p < 0.05) differences in comprehensive faecal metabolome in the patients’ cohort as a whole and in patients with a history of HAEC. Pathway analysis revealed the most impact on amino sugar, lysine, sialic acid, hyaluronan and heparan sulphate metabolism in HD, as well as impaired tyrosine metabolism in HAEC group. Those changes imply disruption of intestinal mucosal barrier due to glycosaminoglycan breakdown and dysbiosis as major metabolic changes in patients’ group and should be further explored for potential diagnostic or treatment targets.